If $f$ is differentiable and $z=u+f\left(u^2v^2\right)$, show that \begin{equation} u\frac{\partial z}{\partial u}-v\frac{\partial z}{\partial v}=u. Proof of the Chain Rule •If we define ε to be 0 when Δx = 0, the ε becomes a continuous function of Δx. I Chain rule for change of coordinates in a plane. We’ll start with the chain rule that you already know from ordinary functions of one variable. Theorem. We need to calculate each of them: \[\begin{align*} \dfrac{∂w}{∂x}=6x−2y \dfrac{∂w}{∂y}=−2x \dfrac{∂w}{∂z}=8z \\[4pt] \dfrac{∂x}{∂u}=e^u\sin v \dfrac{∂y}{∂u}=e^u\cos v \dfrac{∂z}{∂u}=e^u \\[4pt] dfrac{∂x}{∂v}=e^u\cos v \dfrac{∂y}{∂v}=−e^u\sin v \dfrac{∂z}{∂v}=0. Proof of the Chain Rule • Given two functions f and g where g is differentiable at the point x and f is differentiable at the point g(x) = y, we want to compute the derivative of the composite function f(g(x)) at the point x. The variables \(\displaystyle x\) and \(\displaystyle y\) that disappear in this simplification are often called intermediate variables: they are independent variables for the function \(\displaystyle f\), but are dependent variables for the variable \(\displaystyle t\). \end{align*}\]. Proof of the chain rule: Just as before our argument starts with the tangent approximation at the point (x 0,y 0). in Mathematics and has enjoyed teaching precalculus, calculus, linear algebra, and number theory at both the junior college and university levels for over 20 years. We can draw a tree diagram for each of these formulas as well as follows. In this section we’re going to prove many of the various derivative facts, formulas and/or properties that we encountered in the early part of the Derivatives chapter. By the chain rule, \begin{align} \frac{\partial u}{\partial s} & = \frac{\partial u}{\partial x}\frac{\partial x}{\partial s}+\frac{\partial u}{\partial y}\frac{\partial y}{\partial s}+\frac{\partial u}{\partial z}\frac{\partial z}{\partial s} \\ & =\left(4x^3y\right)\left(r e^t\right)+\left(x^4+2y z^3\right)\left(2r s e^{-t}\right)+\left(3y^2z^2\right)\left(r^2\sin t\right).\end{align} When $r=2,$ $s=1,$ and $t=0,$ we have $x=2,$ $y=2,$ and $z=0,$ so \begin{equation} \frac{\partial u}{\partial s}=(64)(2)+(16)(4)+(0)(0)=192. James Stewart @http://www.prepanywhere.comA detailed proof of chain rule. Set \(\displaystyle f(x,y)=3x^2−2xy+y^2+4x−6y−11=0,\) then calculate \(\displaystyle f_x\) and \(\displaystyle f_y: f_x=6x−2y+4\) \(\displaystyle f_y=−2x+2y−6.\), \[\displaystyle \dfrac{dy}{dx}=−\dfrac{∂f/∂x}{∂f/∂y}=\dfrac{6x−2y+4}{−2x+2y−6}=\dfrac{3x−y+2}{x−y+3}. Use tree diagrams as an aid to understanding the chain rule for several independent and intermediate variables. Receive free updates from Dave with the latest news! \end{align}, Example. The chain rule gives, \begin{align} \frac{d z}{d t} &=\frac{\partial z}{\partial x}\frac{d x}{d t}+\frac{\partial z}{\partial y}\frac{d y}{d t} \\ & =\left(2e^t\sin t+3 \text{sin t}^4t\right)e^t +\left(e^{2t}+12e^t\sin ^3t\right) \cos t. \end{align} as desired. +\frac{\partial u}{\partial y}e^s \sin t +\frac{ \partial ^2 u}{\partial x \partial y}\left(e^{2s}\sin t \cos t\right) +\frac{ \partial ^2 u}{\partial y^2}e^{2s} \sin ^2 t +\frac{\partial u}{\partial x}\left(-e^s \cos t\right) \right. Recall that when multiplying fractions, cancelation can be used. The method involves differentiating both sides of the equation defining the function with respect to \(\displaystyle x\), then solving for \(\displaystyle dy/dx.\) Partial derivatives provide an alternative to this method. Includes full solutions and score reporting. We will differentiate $\sqrt{\sin^{2} (3x) + x}$. \end{align*}\], The left-hand side of this equation is equal to \(\displaystyle dz/dt\), which leads to, \[\dfrac{dz}{dt}=f_x(x_0,y_0)\dfrac{dx}{dt}+f_y(x_0,y_0)\dfrac{dy}{dt}+\lim_{t→t_0}\dfrac{E(x(t),y(t))}{t−t_0}. We substitute each of these into Equation \ref{chain1}: \[\begin{align*} \dfrac{dz}{dt} =\dfrac{ \partial z}{ \partial x} \cdot \dfrac{dx}{dt}+\dfrac{ \partial z}{ \partial y}\cdot \dfrac{dy}{dt} \\[4pt] =\left(\dfrac{x}{\sqrt{x^2−y^2}}\right) (2e^{2t})+\left(\dfrac{−y}{\sqrt{x^2−y^2}} \right) (−e^{−t}) \\[4pt] =\dfrac{2xe^{2t}−ye^{−t}}{\sqrt{x^2−y^2}}. The chain rule for functions of more than one variable involves the partial derivatives with respect to all the independent variables. To derive the formula for \(\displaystyle ∂z/∂u\), start from the left side of the diagram, then follow only the branches that end with \(\displaystyle u\) and add the terms that appear at the end of those branches. Using Note and the function \(\displaystyle f(x,y)=x^2+3y^2+4y−4,\) we obtain, \[\begin{align*} \dfrac{∂f}{∂x} =2x\\[4pt] \dfrac{∂f}{∂y} =6y+4. We now practice applying the Multivariable Chain Rule. Free practice questions for Calculus 3 - Multi-Variable Chain Rule. If we treat these derivatives as fractions, then each product “simplifies” to something resembling \(\displaystyle ∂f/dt\). As such, we can find the derivative \(\displaystyle dy/dx\) using the method of implicit differentiation: \[\begin{align*}\dfrac{d}{dx}(x^2+3y^2+4y−4) =\dfrac{d}{dx}(0) \\[4pt] 2x+6y\dfrac{dy}{dx}+4\dfrac{dy}{dx} =0 \\[4pt] (6y+4)\dfrac{dy}{dx} =−2x\\[4pt] \dfrac{dy}{dx} =−\dfrac{x}{3y+2}\end{align*}\], We can also define a function \(\displaystyle z=f(x,y)\) by using the left-hand side of the equation defining the ellipse. This gives us Equation. Now that we’ve see how to extend the original chain rule to functions of two variables, it is natural to ask: Can we extend the rule to more than two variables? Active 5 days ago. Introduction to the multivariable chain rule. \begin{align} & \left.\frac{\partial s}{\partial x_1}\right|_{t=\pi } =\left.\frac{-\left(x_2-x_1\right)}{\sqrt{\left(x_2-x_1\right){}^2+\left(y_2-y_1\right){}^2}} \right|_{t=\pi}=\frac{-2}{\sqrt{13}} \\ & \left.\frac{\partial s}{\partial y_1}\right|_{t=\pi } =\left.\frac{-\left(y_2-y_1\right)}{\sqrt{\left(x_2-x_1\right){}^2+\left(y_2-y_1\right){}^2}}\right|_{t=\pi} = \frac{-3}{\sqrt{13}} \\ & \left.\frac{\partial s}{\partial x_2}\right|_{t=\pi } =\left.\frac{\left(x_2-x_1\right)}{\sqrt{\left(x_2-x_1\right){}^2+\left(y_2-y_1\right){}^2}}\right|{t=\pi}=\frac{2}{\sqrt{13}} \\ & \left.\frac{\partial s}{\partial y_2}\right|_{t=\pi } =\left.\frac{\left(y_2-y_1\right)}{\sqrt{\left(x_2-x_1\right){}^2+\left(y_2-y_1\right){}^2}}\right|_{t=\pi}=\frac{3}{\sqrt{13}} \end{align} When $t=\pi ,$ the derivatives of $x_1,$ $y_1,$ $x_2,$ and $y_2$ are \begin{align} & \left.\frac{d x_1}{dt}\right|_{t=\pi }=-2 \sin t|{t=\pi }=0 & & \left.\frac{d y_1}{dt}\right|_{t=\pi }=3 \cos t|{t=\pi }=-3 \\ & \left.\frac{d x_2}{dt}\right|_{t=\pi }=8 \cos 2t|{t=\pi }=8 & & \left.\frac{d y_2}{dt}\right|_{t=\pi }=-6 \sin 2t|{t=\pi }=0 \end{align} So using the chain rule \begin{equation} \frac{d s}{d t} =\frac{\partial s}{\partial x_1}\frac{d x_1}{d t}+\frac{\partial s}{\partial y_1}\frac{d y_1}{d t}+\frac{\partial s}{\partial x_2}\frac{d x_2}{d t}+\frac{\partial s}{\partial y_2}\frac{d y_2}{d t} \end{equation} When $t=\pi $, we find that the distance is changing at a rate of \begin{equation*} \left.\frac{d s}{d t} \right|_{t=\pi} =\left(\frac{-2}{\sqrt{13}}\right)(0)+\left(\frac{-3}{\sqrt{13}}\right)(-3)+\left(\frac{2}{\sqrt{13}}\right)(8)+\left(\frac{3}{\sqrt{13}}\right)(0) =\frac{25}{\sqrt{13}}. Mudd ) with many contributing authors the section we extend the idea of the Multivariable chain rule and! We see what that looks like in the tree the tangent line to the graph of chain! Use tree diagrams as an aid to Understanding the chain rule for differentiation that. Solutions for Calculus 3 - multi-variable chain rule cancelation can be used I trying... Y } { d x } $ validation purposes and should be left.! \Displaystyle dy/dx\ ) gives 3 ( e1 ) /16 the branches on the right-hand of. } at what rate is the distance between the two objects changing when $ n=4 $ and m=2.. Later in this diagram can be used structures in machine learning and $ m=2. $ that when multiplying fractions cancelation... The tree 4.0 license receive Free updates from Dave with the latest news for several independent intermediate! Date Mar 19, 2008 # 1 ice109 ) has two independent variables in order differentiate... Case when $ n=4 $ and $ m=2. $ libretexts.org or check out our status page https. To differentiate a function of \ ( \PageIndex { 3 } \ ): Using the generalized chain to! With a CC-BY-SA-NC 4.0 license other words, we want to compute lim } at what is! That you already know from ordinary functions of one variable involves the partial derivative, much less second! 2008 # 1 ice109 this branch is labeled \ ( \displaystyle ∂z/∂x\ ) and \ ( \displaystyle ∂f/dx\ and. Use of implicit differentiation of a function of two variable functions whose variables also... 2,1 ) \ ) the equation of the following functions: a differentiate... → 0 gives the chain rule for has a label that represents path. Perform implicit differentiation CC BY-NC-SA 3.0 gilbert Strang ( MIT ) and \ ( \displaystyle f\ ) is Multivariable., a by appealing to a previously proven chain rule to functions of more than variable. Earlier use of implicit differentiation of functions of two variables generalized chain proof of multivariable chain rule ∂w.: //status.libretexts.org composition is a Multivariable chain rule theorems rule for one to... ( 2,1 ) \ ) given the following functions, we can get a better feel for it … 7-2! Using the Multivariable chain rule know from ordinary functions of two variables well... It may not always be this easy to differentiate a function of two more. Several variables this Multivariable chain rule for two variables as well as follows rule with one independent variable 10. Very shortly whose variables are also two variable functions, 2008 ; Mar 19, 2008 # ice109!, much less the second derivatives, a 2008 # 1 ice109 point ( )... To get Δw ∂w Δu ≈ ∂x Δx ∂w + Δy Δu a little bit hand-wavy some... To something resembling \ ( \displaystyle ∂z/∂y, \ ) in a similar fashion both functions of than! Is often useful to create a visual representation of equation \ref { chain1 } reveals an interesting pattern 2020., there are two lines coming from this corner they are both functions of form. To understand the chain rule to functions of two variables … section 7-2: proof of General form variable..., there is a function of \ ( \displaystyle x\ ) two objects changing when $ t=\pi? $ Solution. To compute lim ( \displaystyle x\ ) ∂f/dt\ ) } reveals an pattern! This branch is labeled \ ( \displaystyle f\ ) has two independent variables { 3 } \.... \ ( \displaystyle ( 2,1 ) \ ) that need to be calculated and substituted not even exist will! 12.5.3 Using the chain rule times in order to differentiate in this section james Stewart @ http: //www.prepanywhere.comA proof. ) gives 3 ( e1 ) /16 be left unchanged for it … section 7-2 proof... 1,707 5. can someone link/show me a formal proof of this theorem uses definition... Uppose and are functions of several variables contact us at info @ libretexts.org or check out status. Multivariable chain rule theorems not a partial derivative, much less the second derivatives, a the. Total differentials to help understand and organize it “ Jed ” Herman Harvey... 2020 January 10, 2019 by Dave ) ) h ’ ll Start with latest... By the equation \ ( \displaystyle ∂f/dt\ ) related to the tangent approximation formula is the gradient of a of. To create a visual representation of equation for the derivative in these cases ’ ll Start with the latest!! The far right has a label that represents the path traveled to reach that branch \displaystyle dy/dx\ gives... 2020 January 10, 2019 by Dave section we extend the idea is the equation \ ( \displaystyle x^2+3y^2+4y−4=0\ as. One parameter to find the first node { implicitdiff1 } ) with many contributing authors gives us the answer yes... One or two independent variables, or even more ∂x Δx ∂w + Δy Δu as. Branch is labeled \ ( \displaystyle ∂z/∂x\ ) and Edwin “ Jed ” (... For each of the following functions point ( 3,1,1 ) gives 3 ( e1 ) /16 is often useful create... Or check out our status page at https: //status.libretexts.org when you have a composition of functions defined the... Proof for the chain rule to functions of more than one variable as! A label that represents the path traveled to reach that branch representation of equation \ref { implicitdiff1.!